2018
DOI: 10.29328/journal.ijceo.1001011
|View full text |Cite
|
Sign up to set email alerts
|

The management of Irvine-Gass Syndrome in a patient using Inhaler Steroid

Abstract: Irvine-Gass syndrome, is one of the most common causes of painless decrease in vision following even uneventful cataract surgery. It usually responds well to medical therapy, but, there are no widely acceptedconsensus on the effi cacy of various therapeutic options for the treatment of Irvine-Gass syndrome. The patient presenting in this case report, has systemic hypertension and chronic obstructive pulmonary disease and he use oral anti-hypertension medication and inhaler steroid. He diagnosed as Irvine-Gass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…14 Triamcinolone acetonide (TA), used off-label and administered by intravitreal (4 mg/0.1 mL) or sub-tenon (40 mg/mL) injections, has been effectively used in clinical practice for over two decades. 2,3,5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Triamcinolone acetonide (TA), used off-label and administered by intravitreal (4 mg/0.1 mL) or sub-tenon (40 mg/mL) injections, has been effectively used in clinical practice for over two decades. 2,3,5…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Triamcinolone acetonide (TA), used off-label and administered by intravitreal (4 mg/0.1 mL) or sub-tenon (40 mg/mL) injections, has been effectively used in clinical practice for over two decades. 2,3,5 All intraocular corticosteroids share the same main complications, which include cataract development and a variable and dose dependent increase in intraocular pressure (IOP), sometimes to a level compatible with ocular hypertension (OHT). [6][7][8][9][10][11][12][13] Nearly 35% of the general population respond to corticosteroids, developing some degree of IOP increase following local treatment with corticosteroids.…”
Section: Introductionmentioning
confidence: 99%
“…Altintas et al [26], reported a signi icant reduction in macular thickness with a single Ozudex implantation from 733 u to 197 u in eyes with unresponsive to intravitreal Anti-VEGF who is using inhaler steroid. This report showed that PCME can be developed even under systemic steroid treatment and intravitreal Ozudex implantation can be effective in such a dif icult patient.…”
Section: Corticosteroid Treatmentmentioning
confidence: 99%